Group farming and productivity in the Muda Agricultural Development Authority of Malaysia (Journal of Business Management and Accounting, 2012)
The paddy sector is a strategic sector in Malaysia. This is due to its importance in the context of rice self-sufficiency, income generation and job opportunities especially for the rural population. The Malaysian government has set the goal of achieving self- sufficiency level in rice production at about 65-70% of local consumption. In order to achieve the objective, the government has implemented many strategies, the group farming project in Muda Agricultural Development Area (MADA) is one such strategy. The study was conducted on four MADA areas representing three schemes, namely the 10 tones Project, Estate Paddy Project, and Model Farm Project. The proportionate multistage stratified random sampling technique involving the area sampling method and the systematic method was employed to select 664 respondents. An econometric model and other statistical techniques were used to estimate the effects of group farming project on productivity and farmersâ€™ income. The study shows that, in terms of economic return dimension, Model Farm Project is more successful in increasing the paddy production. The study makes a number of suggestions for improving the effectiveness of group farming projects. Recommendations are included in the project planning and implementation of group farming, and the importance of subsidy on paddy production for farmers in the study area.